Performance of asphalt rubber mixture overlays to mitigate reflective cracking - Thives, Liseane Padilha (2022)
Adequately predicting overlay behaviour is essential for flexible pavement rehabilitation to reach the predicted lifespan. Reflective cracking is one of the main failure mechanisms affecting overlay performance. This failure may occur due to cracks in the lower layers that propagate to the overlay due to traffic loads, temperature variations, shrinkage cracking of cement-treated layers, and subgrade movements. This work aims to assess the reflective cracking phenomenon of asphalt rubber mixtures as an overlay through laboratory tests and numerical simulation. Four-point bending equipment and the reflective crack device were used to perform the laboratory tests. A numerical simulation through the finite elementmethodwas accomplished to estimate the vonMises strain and develop reflective cracking fatigue laws. The results showed that the asphalt rubber mixtures are suitable for extending overlay lifespan considering reflective cracking. The evaluated asphalt rubber mixtures presented reflective cracking resistance almost eight times greater than the conventional ones.